WEEK WITHOUT WALLS: A 21ST CENTURY CLASSROOM IMPLEMENTATION AT TERTIARY LEVEL - Soo Kum Yoke; Nor Haniza Hasan; Hazwati Hashim; Nadiah Yahyauddin, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
This paper uses a descriptive approach to investigate the implementation of 21st-century classroom learning at the tertiary level. The action research observed the use of digital technology in a universityâ€™s â€œWeek Without Wallsâ€ initiative. The purpose was to find out what activities were carried out in the â€œWeek Without Wallsâ€ and how they were implemented in relation to 21st-century education learning. A total number of 17 lecturersâ€™ teaching and learning activities were observed during a one-week university initiative of out-of-classroom â€œWeek Without Wallsâ€ implementation. Lecturers were given directions to prepare their activities outside the classroom walls in any form or manner of their choice. The results showed that the majority of lecturers used digital technologies to carry out their activities during the week with the highest application being online learning and WhatsApp mobile sharing. This provided a strong indication that the possibilities of the use of digital technologies for teaching and learning are tremendous and highly recommended for the implementation of 21st century classroom learning.